2016
DOI: 10.1136/bmjopen-2016-012144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with parental concerns about development detected by theParents’ Evaluation of Developmental Status (PEDS)at 6-month, 12-month and 18-month well-child checks in a birth cohort

Abstract: ObjectivesEarly identification of developmental vulnerability is vital. This study aimed to estimate the prevalence of moderate or high developmental risk on the Parents' Evaluation of Developmental Status (PEDS) at 6-month, 12-month and 18-month well-child checks; identify associated risk factors; and examine documentation of the PEDS at well-child checks.Design, participantsA prospective birth cohort of 2025 children with 50% of those approached agreeing to participate. Demographic data were obtained via que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 31 publications
5
27
0
1
Order By: Relevance
“…This aligns with the theoretical frameworks of cumulative risk and intersectionality of risk factors in relation to early childhood development 18–20. Yet, while health service patterns according to socioeconomic disadvantage and developmental vulnerability have been described separately,2 3 12 the combined effect on the use of health services by a preschool-aged child of being developmentally vulnerable and socioeconomic disadvantaged has not been examined.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…This aligns with the theoretical frameworks of cumulative risk and intersectionality of risk factors in relation to early childhood development 18–20. Yet, while health service patterns according to socioeconomic disadvantage and developmental vulnerability have been described separately,2 3 12 the combined effect on the use of health services by a preschool-aged child of being developmentally vulnerable and socioeconomic disadvantaged has not been examined.…”
Section: Introductionsupporting
confidence: 56%
“…Around one in five Australian preschool children have physical, socioemotional and learning difficulties that require additional support for school success—that is, they are ‘developmentally vulnerable’ 1–4. Children who developmentally vulnerable are more likely to have poor educational outcomes in primary school and early high school 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…Only a small minority (14%) of carers of all children aged 4-5 years reportedly saw a MCHN in the previous year. This is consistent with the drop off in attendance after 18 months reported in Australia (3). This represents a missed opportunity in detection of this developmental vulnerability and referral for early intervention in the 12 months prior to school which may impact on school readiness particularly for children who are developmentally vulnerable and disadvantaged.…”
Section: Use Of Any Health Services By Developmental Vulnerability Ansupporting
confidence: 83%
“…This also highlights a caregiver need for services that support children's speech and language and behaviour in ACCHs and mainstream services. Previous research using the PEDS in a culturally and linguistically diverse and low socioeconomic status cohort of children in Australia showed that developmental risk increased with the age [33]. Similarly, in our cohort, children in the older age group (4.5 to 8 years) had the highest prevalence of developmental risk.…”
Section: Discussionsupporting
confidence: 69%
“…Due to the amount of missing data we used multiple imputation to account for the missing values for the risk factors. Under the assumption that the missing data were missing at random, multilevel multiple imputation was performed using REALCOM-IMPUTE software [33]. We created 50 imputed data sets, which incorporated variability due to uncertainty in the exact values, with a burn-in period of 2500 iterations and 500 iterations between imputations.…”
Section: Discussionmentioning
confidence: 99%